2019
DOI: 10.1111/luts.12247
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron induces relaxant effects via cAMP signaling‐dependent and ‐independent pathways in detrusor smooth muscle

Abstract: Objective: We previously found that mirabegron exerts a relaxant effect in the presence of the β 3 -adrenoceptor antagonist SR58894A during carbachol-induced contraction in human and pig detrusor. The aim of this study was to explore the possible mechanism underlying the relaxant effects of mirabegron using detrusor smooth muscle. Methods: Human tissue was obtained from urinary bladders of patients undergoing radical cystectomy at Kyushu University and Harasanshin Hospital. Pig tissue was obtained from an abat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Furthermore, pre-incubation with adenylate cyclase inhibitor SQ22536 markedly suppressed both of these effects [92]. However, Maki et al recently reported a milder effect of SQ22536 on human and pig pre-contracted detrusor strips treated with mirabegron supporting the hypothesis of a cAMP-independent mechanism, potentially via activation of myosin light chain phosphatase [93]. Along the same line, Frazier et al previously showed that only Rp-cAMPS, among other PKA inhibitors had a small significant effect on isoproterenol responses against passive tension on non-contracted rat bladder strips, not supporting a major role for cAMP and/or PKA in β-AR-mediated bladder relaxation.…”
Section: β3-ar As Therapeutic Targetmentioning
confidence: 99%
“…Furthermore, pre-incubation with adenylate cyclase inhibitor SQ22536 markedly suppressed both of these effects [92]. However, Maki et al recently reported a milder effect of SQ22536 on human and pig pre-contracted detrusor strips treated with mirabegron supporting the hypothesis of a cAMP-independent mechanism, potentially via activation of myosin light chain phosphatase [93]. Along the same line, Frazier et al previously showed that only Rp-cAMPS, among other PKA inhibitors had a small significant effect on isoproterenol responses against passive tension on non-contracted rat bladder strips, not supporting a major role for cAMP and/or PKA in β-AR-mediated bladder relaxation.…”
Section: β3-ar As Therapeutic Targetmentioning
confidence: 99%
“…In conclusion, data suggest that the therapeutic success of β 3adrenoceptor agonists in the treatment of OAB syndromes involves activation of an EPAC1-PKC intracellular pathway downstream of cAMP production, resulting in adenosine release, via ENT1, from the detrusor and retrograde activation of inhibitory A 1 receptors on cholinergic nerves. The adenosine-mediated inhibitory effect on cholinergic neurotransmission (this study; Silva et al, 2017) may add to cAMP-dependent and -independent mechanisms whenever β 3adrenoceptor agonists reach the micromolar concentration range required to cause direct relaxation of detrusor smooth muscle fibres (Maki et al, 2019;Michel & Korstanje, 2016). Although still premature, manipulation of the activity of EPAC1 and conventional PKC isoforms may provide additional therapeutic targets to improve bladder overactivity, alongside β 3 -adrenoceptor agonists, also counting on the possibility that the cAMP-dependent EPAC1 signalling may prevent fibroblast-induced irreversible bladder remodelling that is often observed as a consequence of bladder obstruction and/or chronic overactivation (see Certal et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Intracellular effects of cAMP are most often attributed to protein kinase A (PKA; Wang et al, ). However, detrusor relaxation owing to downstream activation of the AC/PKA pathway by β‐adrenoceptors has been questioned (Frazier, Mathy, Peters, & Michel, ; Maki et al, ), raising the hypothesis that PKA‐independent effects are also involved (de Rooij et al, ; Kawasaki et al, ; reviewed in Dekkers, Racké, & Schmidt, ). The exchange protein directly activated by cAMP (EPAC) is a cAMP‐regulated guanine nucleotide exchange factor that favours GDP/GTP exchange and activation of small Ras‐like GTPases (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirabegron is a drug that is used in patients with overactive bladder and acts by stimulating selective beta-3 receptors. Mirabegron increases the capacity of the bladder by relaxing mechanism and affecting its filling function without affecting its contractility or flow rates [10,11]. Animal experiments have also demonstrated dilatation of the ureter and a decrease in ureteral intraluminal pressure with the use of mirabegron [12].…”
Section: Discussionmentioning
confidence: 99%